Exploring the relationship between college students' understanding of particle theory of matter and their conceptual understanding of vapor pressure - İşcan, Meltem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
This mixed method study mainly explores the association between first-year college students’ understanding of particulate nature of matter (PNM) and their understanding of vapor pressure. The goal was to identify and describe the levels of understanding of specific vapor pressure concepts of a group of participants with a high understanding of PNM and a group with a low understanding of PNM. The sample of this study was 48 first-year college students who were enrolled in General Chemistry I course. Data were collected through a diagnostic test about the PNM and interviews on vapor pressure. Data obtained from diagnostic tests and interviews were coded and analyzed by using qualitative and quantitative methods. Different aspects of vapor pressure were evaluated by giving numeric points to each participant’s responses in the quantitative analysis. Each participant’s level of conceptual understanding about specific vapor pressure concepts was identified in the qualitative analysis. According to data analysis results, it was concluded that there was a statistically significant difference between the groups of high understanding of PNM and low understanding of PNM in terms of their understanding of vapor pressure. Participants with a high understanding of PNM were more likely to develop a scientific understanding in vapor pressure.
Keywords: Chemistry -- Study and teaching (Higher); Matter -- Constitution.